Design and Construct Water Levitation Module with Arduino Uno - Zaiul Farhan; Antonius Suhartomo (Journal of Electrical And Electronics Engineering, 2016)
Sound is exotic thing that ready to be researched and explored. Although many researches were done on this theme, there are still many things that can be obtained when researching about sound. For example, levitate things with ultrasonic frequency. It is amazing that sound, which is like a vibe, can levitate things. From that idea, the writer fascinated to construct the water levitation circuit. In this project, with Arduino and a strobe light, the writer creates a design that makes it possible to see the water levitation phenomenon with using audible frequency.The device provides an optical illusion, so the blink of LED that hit droplets from tube, pumped by water pump, looks like levitate with human eyes.  This method can show the variations of water levitation phenomena with correct time setting of the blinking LED and frequency setting of the speaker. The synchronization frequency of LED and speaker will make the water stay. But, frequency of the LED higher than the speaker, then it will make droplets ascend and vice versa, if frequency of LED lower than the speaker, it will make droplets descend as normally it does.Keywords: strobe light, sound, droplets, levitation, optical illusion, LED.